Птицы над сушей и морем: Глобальный обзор миграций птиц - Карри-Линдал Кай (Мысль, 1984)
Экземпляры: ЧЗ (20181022) / Инвентарный номер: 9467 / Цена: 2.80 / Сис.шифр: 28.6 / Авт.знак: К 26 / ГРНТИ: 34 / ББК: 28.693.35